Enhancing Anti-Hyperpigmentation Efficacy: A Review on Herbal Nanodelivery System - Pebriani, Ni Luh Gede Wiwin; Mauludin, Rachmat; Kurniati, Neng Fisheri (Current Nanomaterials, 2026)
Hyperpigmentation refers to a condition characterized by excessive skin pigmentation, leading to darkened areas on the skin. This condition can significantly affect physical appearance and have adverse effects on emotional and psychological well-being. The use of commercial skinlightening products for hyperpigmentation therapy often entails significant side effects, prompting the exploration and development of herbal products as alternative anti-hyperpigmentation agents. Herbs act as anti-hyperpigmentation agents through various mechanisms, including inhibiting the expression and activity of tyrosinase, as well as reducing the uptake and distribution of melanosomes. The advancement of nanoparticle delivery systems represents a significant stride in enhancing the efficacy of herbal compounds, overcoming the limitations associated with conventional phytochemical formulations. Herbal plants incorporated into nanoparticle delivery systems demonstrate superior activity as anti-hyperpigmentation agents compared to their conventional extract counterparts. Various nanoparticle formulations employed include zinc oxide and gold nanoparticles, nanovesicles, nanosponges, nanoliposomes, Nanostructured Lipid Carriers (NLC), and Solid Lipid Nanoparticles (SLN). This narrative review aims to explore natural ingredients, diverse nanoparticle formulations, and the impacts of nanoparticle delivery of herbs as anti-hyperpigmentation agents, drawing insights from both preclinical and clinical studies. This review is intended to provide a foundation for the future development of herbal nanoparticle delivery systems.
Keywords: nanoparticle